Altiplano agricultural origins was a process of economic resilience, not hardship: Isotope chemistry, zooarchaeology, and archaeobotany in the Titicaca Basin, 5.5-3.0 ka - Luis Flores-Blanco; Morgan Hall; Luisa Hinostroza; Jelmer Eerkens; Mark Aldenderfer; Randall Haas (PLoS ONE, 2025)
Prevailing models of agricultural origins tend to envision that economic hardship drove the transition from foraging to farming economies. Growing human populations and the depletion of high-ranked animal resources forced humans into increasingly intensive and dependent relationships with plant foods. Current evidence from the Andean Altiplano (High Plateau, 3800 masl) identifies the Terminal Archaic Period (5.0–3.5 cal. ka) as the period of economic transition from Archaic foraging economies to Formative Period agro-pastoral economies. Consistent with models of agricultural origins, isotope chemistry (δ13Ccollagen, δ13Capatite, δ15Ncollagen) of human bone samples from 16 individuals from the Terminal Archaic sites of Kaillachuro and Jiskairumoko (5.3–3.0 cal. ka) indicates that C3 plants comprised approximately 84% of the dietary protein. Archaeobotanical data show that chenopods may have been the most important subsistence resource, and zooarchaeological remains indicate that protein was derived from camelid meat. Inconsistent with the working model of plant intensification, the Terminal Archaic diets reported here are statistically indistinguishable from previously published values of Early—Late Archaic (9.0–6.5 cal. ka) individuals in the same region, which also show approximately 84% of protein coming from plants. Rather than being a process of dramatic dietary change and economic hardship, the agricultural transition on the Altiplano appears to have been one of remarkable resilience in which plant:meat ratios remained relatively stable over six millennia, spanning the transition from Archaic foraging and hunting to Formative farming and herding economies. Plant and animal domestication on the Altiplano thus represents a process of economic sustainability rather than one of food insecurity and hardship, as many prevalent agricultural origins models would suggest.